The corruption of co-design political and social conflicts in participatory design thinking - Busch, Otto von 1975-; Palmås, Karl (Routledge, 2023)
Designers are often depicted as social change agents that serve the good in the world. Similarly, codesign tends to be described as a democratic mode of creativity that is somehow beyond reproach. But is change a virtue in itself, and do participatory practices always produce socially beneficial outcomes?